1975
DOI: 10.1128/jcm.1.3.294-297.1975
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate fermentation plate medium for confirmation of Neisseria species

Abstract: A carbohydrate fermentation plate medium is described for rapid and reliable confirmation of Neisseria gonorrhoeae, N. meningitidis, and other Neisseria species. The medium is based on a modification of NYC (U.S. Patent 3,846,241) medium, originally designed for the isolation of pathogenic Neisseria (3). A total of 715 clinical isolates were tested for their carbohydrate fermentation reactions on the medium, in parallel with cystine-Trypticase agar medium. In 82% of the strains tested, results were in agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Premarket evaluations of 54 strains of N. gonorrhoeae, 40 strains of N. meningitidis (including serotypes A, B, C, X, Y, Z, W135, and nontypable strains), 8 strains of N. lactamica, and 2 strains of Branhamella catarrhalis indicated that the Identicult-Neisseria correlated almost 100% with modified New York City fermentation medium (2,5). All 54 isolates of N. gonorrhoeae were positive for PAP and negative for GAP and BDG.…”
mentioning
confidence: 99%
“…Premarket evaluations of 54 strains of N. gonorrhoeae, 40 strains of N. meningitidis (including serotypes A, B, C, X, Y, Z, W135, and nontypable strains), 8 strains of N. lactamica, and 2 strains of Branhamella catarrhalis indicated that the Identicult-Neisseria correlated almost 100% with modified New York City fermentation medium (2,5). All 54 isolates of N. gonorrhoeae were positive for PAP and negative for GAP and BDG.…”
mentioning
confidence: 99%
“…It is evident from the number of recent publications suggesting modifications for improving the reliability of the sugar degradation tests that they still pose a significant problem for many diagnostic laboratories (2,4,10,12,17,20,21). In several comparative studies by different workers to determine the most reliable of the various types of sugar utilization tests, the numbers of positives obtained, even when the same type of test was used, varied as much as 30 to 35% (3,14,16).…”
mentioning
confidence: 99%
“…The most commonly used method is carbohydrate degradation reactions in CTA. The CTA medium not only requires 24 to 48 h of incubation, but also has been found to be inadequate in certain cases owing to the failure of occasional strains of gonococci to produce acid from glucose (6,11,16,19,25). Consequently, numerous methods have been reported in the literature which are claimed to be both sensitive and rapid (5,11,12,16,19,24,26).…”
Section: Resultsmentioning
confidence: 99%